Comparative Transcriptome Analysis of Early- and Late-Bolting Traits in Chinese Cabbage (Brassica rapa) - Wei, Xiaochun; Rahim, Md. Abdur; Zhao, Yanyan; Yang, Shuangjuan; Wang, Zhiyong; Su, Henan; Li, Lin; Niu, Liujing; Harun-Ur-Rashid, Md.; Yuan, Yuxiang; Zhang, Xiaowei (Frontiers in Genetics, 2021)
Chinese cabbage is one of the most important and widely consumed vegetables in China. The developmental transition from the vegetative to reproductive phase is a crucial process in the life cycle of flowering plants. In spring-sown Chinese cabbage, late bolting is desirable over early bolting. In this study, we analyzed double haploid (DH) lines of late bolting (“Y410-1” and “SY2004”) heading Chinese cabbage (Brassica rapa var. pekinensis) and early-bolting Chinese cabbage (“CX14-1”) (B. rapa ssp. chinensis var. parachinensis) by comparative transcriptome profiling using the Illumina RNA-seq platform. We assembled 721.49 million clean high-quality paired-end reads into 47,363 transcripts and 47,363 genes, including 3,144 novel unigenes. There were 12,932, 4,732, and 4,732 differentially expressed genes (DEGs) in pairwise comparisons of Y410-1 vs. CX14-1, SY2004 vs. CX14-1, and Y410-1 vs. SY2004, respectively. The RNA-seq results were confirmed by reverse transcription quantitative real-time PCR (RT-qPCR). A Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of DEGs revealed significant enrichment for plant hormone and signal transduction as well as starch and sucrose metabolism pathways. Among DEGs related to plant hormone and signal transduction, six unigenes encoding the indole-3-acetic acid-induced protein ARG7 (BraA02g009130), auxin-responsive protein SAUR41 (BraA09g058230), serine/threonine-protein kinase BSK11 (BraA07g032960), auxin-induced protein 15A (BraA10g019860), and abscisic acid receptor PYR1 (BraA08g012630 and BraA01g009450), were upregulated in both late bolting Chinese cabbage lines (Y410-1 and SY2004) and were identified as putative candidates for the trait. These results improve our understanding of the molecular mechanisms underlying flowering in Chinese cabbage and provide a foundation for studies of this key trait in related species.